1963
DOI: 10.6028/jres.067a.019
|View full text |Cite
|
Sign up to set email alerts
|

An absolute calibration of the National Bureau of Standards thermal neutron flux

Abstract: The NBS Thermal Neutron Flux has been calibrated in terms of the gold thermal neutron capture cross section. The effective thermal neutron (below cadmium cutoff energy) flux density is estimated to be 4307 ± 2 percent n /cm 2 sec in September 1961. This figure is in agreement with a recent value quoted by the NBS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…The result from this evaluation (JEF-2) is shown in Figs. 13 and 14, normalized around 14 MeV to ENDF/B-VI, support higher cross sections than ENDF/B-VI above 15 MeV but agree very well with ENDF/B-VI at all other energies, specifically around 8 MeV. Data by Buleeva et d35 were measured relative to the H(n,p) cross section and agree reasonably with ENDF/B-VI (see Fig.…”
Section: M3supporting
confidence: 62%
“…The result from this evaluation (JEF-2) is shown in Figs. 13 and 14, normalized around 14 MeV to ENDF/B-VI, support higher cross sections than ENDF/B-VI above 15 MeV but agree very well with ENDF/B-VI at all other energies, specifically around 8 MeV. Data by Buleeva et d35 were measured relative to the H(n,p) cross section and agree reasonably with ENDF/B-VI (see Fig.…”
Section: M3supporting
confidence: 62%
“…Either large experimental halls with thick shielding walls or smaller rooms with thin walls, grid floors, pits below the target and lowmass detector and beam line support are used to reduce the contribution of room-return neutrons [44,45]. The NPL in Teddington (UK) was the first NMI to produce neutron calibration fields in such a low-scatter environment [46]. This facility was used as a model for facilities constructed later on at other NMIs.…”
Section: Production Of Neutron Reference Fieldsmentioning
confidence: 99%
“…Five neutron energies were chosen: 0,144, 0,565, 2,5, 5,O and 14,8 MeV. It was originally suggested that measurement of a specific neutron cross-section should be used for the intercomparison [ 5 ] . In 1979 CCEMRI/CIPM Section 111 proposed that the 235U(n, f) cross-section should be used for the purpose, and that a measurement of the 238U (n, f) cross-section should be included at the three higher energies since it would not be susceptible to thermal neutron background.…”
Section: Introductionmentioning
confidence: 99%